Does the creation of healthy cities promote municipal solid waste management? Empirical research in 284 cities in China - Ma, Qingshan; Zhang, Yutong; Samual, Amoah; Hu, Feng; Touns, Mohcine (Frontiers in Public Health, 2022)
In the context of the COVID-19 pandemic, the creation of healthy cities has become an important measure to deal with global public diseases and public health emergencies, and has had a profound impact on the management of municipal solid waste (MSW). This study exploits the Healthy Cities pilot (HCP) program established in 2016 as a natural experiment, and evaluates its impact on MSW management using the difference-in-difference (DID) method. The estimates show that the collection amount and harmless treatment capacity of MSW were increased by 15.66% and 10.75%, respectively, after the cities were established as pilot healthy cities. However, the harmless treatment rate was decreased by 3.544. This conclusion remains valid in a series of robustness tests, including parallel trend test, placebo test, propensity score matching (PSM)-DID, eliminating the interference of other policies, and eliminating the non-randomness of the policy. Mechanism analysis shows that the HCP program increased the collection amount and harmless treatment capacity of MSW by increasing the expenditure on MSW treatment. However, after a city was established as a pilot healthy city, the unsustainable high expenditure of local government on municipal sanitation led to the decrease in the harmless treatment rate of MSW. Moreover, heterogeneity analysis shows that the HCP program had a stronger impact on MSW management in cities with higher administrative levels, more obvious location advantages, and a larger size. Therefore, it is advisable to use the creation of healthy cities as an important tool to gradually improve MSW management, so as to realize the coordinated development of city construction and human health.